(untitled) (Fiep Bulletin - online, 2016)
INTRODUCTION: Female sexual dysfunction is becoming a problem and an increasingly common complaint in gynecology clinics. It is defined as a disorder in the sexual response or pain associated with sexual intercourse cycle, which results in personal distress and can interfere with both the quality of life and interpersonal relationships of women. OBJECTIVE: To assess the prevalence of sexual dysfunction in young women. METHODS: This study is characterized as transversal and quantitative. 50 young women students in the health area, a private college in western Paraná were interviewed. To meet the objectives the questionnaire Female Sexual Function Index (FSFI), already validated in Brazil was used. Is characterized by auto answered questionnaire consisting of 19 questions that cover six domains of sexual response: desire, arousal, lubrication, orgasm, satisfaction and pain / discomfort. Firstly the questionnaire was explained and only then answered. The participants signed a consent form agreeing to participate in the research being aimed at them a copy of this term. Among the criteria for inclusion are women 18-30 years of age who have an active sex life. The information was kept confidential. All data were indexed in a spreadsheet in Microsoft Excel 2010. RESULTS: Among the 50 women, 76% did not have any kind of sexual dysfunction, 24% had some type of sexual dysfunction. CONCLUSION: Therefore this study concludes that the study population consists of young women there was no prevalence of sexual dysfunction.